A prospective study on awareness of postnatal mothers regarding self and newborn care in a tertiary care centre in Mangalore, Karnataka - Ganiga, Pradeep; Shetty, Sourabha S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Postnatal care is the important portion of maternal health care as it helps to assess the health status of mother and newborn. It promotes to rectify the defect and to identify the progress of the baby that is essential to solve the health issues. Methods: All 100 postnatal women were assessed regarding awareness of self and newborn care using structured questionnaire. Results: In this study maximum number were in age group of 21-25 years (42%). Majority of respondents were literate (88%). Main source of information regarding postnatal and neonatal care is given by health care personnel (49%). 77% cleaned the perineum after defecation and urination. 39% of postnatal mothers practice postnatal exercise. 54% were aware of spacing between two pregnancies. Majority of mothers agreed that colostrum is first breast milk and are aware on giving it to newborn (68%). 78% are aware of exclusively breast feeding baby for 6 months. 79% of postnatal women were aware vaccines prevent diseases in baby. Postnatal mothers had good awareness about self and newborn care. Conclusions: The first 48 hours after delivery is the time when the mother and baby are most vulnerable to morbidity and mortality associated with childbirth. Postnatal care is one of the most important maternal health care for not only prevention of impairment and disabilities, but also for reduction of maternal and neonatal mortality and morbidity.